The Effect of Self-Regulation and Social Support on Student Academic Engagement through Academic Buoyancy - Nora Apriliana; Mungin Eddy Wibowo; Mulawarman (Study Program of Guidance and Counselling, Post Graduate Program, Universitas Negeri Semarang, 2024)
Academic engagement holds important and strategic potential to predict students’ performance progress in carrying out academic tasks and affect their achievement at school. Such an issue motivated the present research to analyze the effect of self-regulation and social support on students' academic engagement through academic buoyancy at the Junior High School (SMP Penggerak) in Surabaya City. A total of 365 samples were selected using a proportional stratified random sampling technique from a total population of 4,170. The self-regulation, social support, academic engagement, and academic buoyancy scales were used to collect their data. The findings suggest that self-regulation and social support could predict academic engagement and buoyancy. Academic engagement was fully mediated between self-regulation and academic buoyancy. Meanwhile, academic engagement was partially mediated by social support and academic buoyancy. Further implications of this research are reviewed in the discussion.